New prospects for the treatment of Spinal Muscular Atrophy - Julita Poleszak; Przemysław Szabat; Marta Szabat; Grzegorz Boreński; Magdalena Wójcik; Joanna Milanowska; Konrad Rejdak (Kazimierz Wielki University, 2019)
Introduction: Spinal muscular atrophy (SMA) is one of the most common genetically determined causes of infant and young child death. The aim of the study: Review of medical literature on therapeutic strategies used in the treatment of SMA. Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed database was carried out using the following keywords: spinal muscular atrophy, nusinersen, zolgensma, reldesemtiv, branaplam, olesoxime. Description: Therapeutic mechanisms in SMA are directed to: 1) modification of pre-mRNA splicing of the SMN2 gene; 2) gene therapy; 3) neuroprotection; 4) improving skeletal muscle function. Summary: The gigantic advances in the development of therapeutical strategies resulted in the approval of two drugs for the treatment of SMA and the commencement of clinical studies on numerous with bundles.